Brain-imaging during an isometric leg extension task at graded intensities - Abeln, Vera; Harig, Alexandra; Knicker, Axel; Vogt, Tobias; Schneider, Stefan (Frontiers in Physiology, 2013)
Imaging the brain during complex and intensive movements is challenging due to the susceptibility of brain-imaging methods for motion and myogenic artifacts. A few studies measured brain activity during either single-joint or low-intensity exercises; however, the cortical activation state during larger movements with increases up to maximal intensity has barely been investigated so far. Eleven right-handed volunteers (22-45 years in age) performed isometric leg extensions with their right leg at 20%, 40%, 60%, 80% and 100% of their maximal voluntary contraction. Contractions were hold for 20 seconds respectively. Electroencephalographic (EEG) and electromyographic (EMG) activity was recorded. Standardized low-resolution brain electromagnetic tomography (sLORETA) was used to localize the cortical current density within the premotor (PMC), primary motor (M1), primary somatosensory (S1) and somatosensory association cortex (SAC). ANOVA was used for repeated measures for comparison of intensities and between the left and right hemispheres. The quality of the EEG signal was satisfying up to 80% intensity. At 100% half of the participants were not able to keep their neck and face muscles relaxed, leading to myogenic artifacts. Higher contralateral versus ipsilateral hemispheric activity was found for the S1, SAC and PMC. M1 possessed higher ipsilateral activity. The highest activity was localized in the M1, followed by S1, PMC and SAC. EMG activity and cortical current density within the M1 increased with exercise intensity. EEG recordings during bigger movements up to submaximal intensity (80%) are possible, but maximal intensities are still hard to investigate when subjects contracted their neck and face muscles at the same time. Isometric contractions mainly involve the M1, whereas the S1, PMC and SAC seem not to be involved in the force output. Limitations and recommendations for future studies are discussed.